THE EFFECT OF ECONOMIC OPENNESS, DEMOCRACY, AND INSTITUTIONAL QUALITY ON INDONESIA EXPORTS TO ASEAN PLUS THREE - Wikantioso Wikantioso (MESP–FEB UNS, 2020)
The ASEAN Charter Agreement and the cooperation of the East Asia Free Trade Area ASEAN+3 provide momentum for ASEAN countries to increase economic openness, strengthen the application of democratic principles, and improve institutional quality to enhance trade cooperation. This study aims to explore the role of economic openness, democracy, and institutional quality in increasing Indonesia's exports to ASEAN countries plus three during the 1996-2017 period using the augmented gravity model. The results showed that the openness of ASEAN+3 to trade (trade% of GDP), democracy, and institutional quality of Indonesia and ASEAN+3 as Indonesia's export destination had positive effects in increasing Indonesia's exports to ASEAN+3. However foreign direct investment in Indonesia and ASEAN+3 does not affect the export.Keywords: Indonesia Trade Gravity Model, Economic Openness, Democracy, Governance Institution, Indonesia's export, ASEAN+3